1976
DOI: 10.1073/pnas.73.12.4329
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal cholesterol uptake from plasma lipoproteins: regulation by corticotropin.

Abstract: The transfer of lipoprotein-bound cholesterol into adrenal cells was examined. Adrenal glands from unstimulated or corticotropin stimulated hypophysectomized rats were incubated with high density lipoprotein (HDL) or low density lipoprotein LDL containing radiolabeled cholesterol. The rate of transfer of labeled cholesterol from HDL into the glands was two to three times greater than from LDL. Corticotropin stimulation increased the transfer of cholesterol from HDL but not LDL. The effects of corticotropin wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(49 citation statements)
references
References 23 publications
1
47
0
1
Order By: Relevance
“…The influence of lipoproteins on steroidogenesis has also been investigated by previous workers, although the majority of studies have been performed from a non-endocrinological perspective with the primary interest being directed towards the biochemistry of cholesterol per se and its subsequent uptake and metabolism, rather than the modulation of glucocorticoid secretion and synthesis. These studies on lipoprotein metabolism have revealed that LDL-cholesterol is preferentially utilised in mice (Faust et al 1977) and human fetal cells , Carr et al 1980, Higashijima et al 1987, whilst HDL-cholesterol is the preferred substrate in rats (Gwynne et al 1976, Andersen & Dietschy 1978, Gwynne & Hess 1980. Studies using bovine adrenocortical cells have demonstrated variable results and few have directly compared the relative effects of HDL and LDL, although preincubation with either lipoprotein increased both basal and ACTH-stimulated steroidogenesis (Koper et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of lipoproteins on steroidogenesis has also been investigated by previous workers, although the majority of studies have been performed from a non-endocrinological perspective with the primary interest being directed towards the biochemistry of cholesterol per se and its subsequent uptake and metabolism, rather than the modulation of glucocorticoid secretion and synthesis. These studies on lipoprotein metabolism have revealed that LDL-cholesterol is preferentially utilised in mice (Faust et al 1977) and human fetal cells , Carr et al 1980, Higashijima et al 1987, whilst HDL-cholesterol is the preferred substrate in rats (Gwynne et al 1976, Andersen & Dietschy 1978, Gwynne & Hess 1980. Studies using bovine adrenocortical cells have demonstrated variable results and few have directly compared the relative effects of HDL and LDL, although preincubation with either lipoprotein increased both basal and ACTH-stimulated steroidogenesis (Koper et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Although the adrenal gland can synthesize cholesterol, the major source of cholesterol for steroidogenesis is circulating lipoproteins (8,9). Cholesterol is acquired from circulating HDL by selective uptake via the scavenger receptor class B type I (SR-BI), and from circulating LDL by endocytosis mediated by the LDL receptor (LDLR) (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Rat luteal and adrenal cells use highdensity lipoprotein (HDL) in preference to low-density lipoprotein (LDL) for the provision of cholesterol substrate (Gwynne, Mahaffee, Brewer & Ney, 1976;Andersen & Dietschy, 1978;Schuler et ai, 1981;Bruot, Wiest & Collins, 1982 (Winkel, Snyder, MacDonald & Simpson, 1980;Carr etai, 1980Carr etai, , 1981Tureck & Strauss, 1982). Incubation of these cells with HDL either has no effect or causes an actual decrease in steroid synthesis (Tureck & Strauss, 1982), perhaps due to promotion of cholesterol efflux (Wu & Baily, 1980 (Savion, Laherty, Cohen, Lui & Gospodarowicz, 1982).…”
Section: Introductionmentioning
confidence: 99%